Raising Awareness of Indonesia’s Climate Change Mitigation by Social Media Campaign - Juan Malik Frederick Turpyn; Anggaraksa Adiwitya (Communicare : Journal of Communication Studies, 2021)
Climate change is a big concern that must be realized because it has become a problem in various sectors both at the international, regional, national and local levels. The occurrence of climate change will certainly also affect the occurrence of extreme weather and disasters - disasters that are not wanted by the public at large. However, the level of public awareness of the bad climate change is still fairly low due to the lack of knowledge about climate change. People can play a role in dealing with climate change, and be actors in mitigating these changes. The use of public communication can increase public awareness and participation in adaptation and mitigation actions on climate change can be realized in many ways, one of which is campaigning to the public. The purpose of this research is to find out how the implementation of social media campaigns in raising awareness of Indonesia's climate change mitigation in the future. The research method that will be used is qualitative with data collection techniques used is Focus Group Discussion, document studies and observations on the intended social media accounts. Researchers did simple research by creating social media accounts to conduct campaigns on the SDGs' points on climate change. The result of this research is the implementation of social media campaigns in raising awareness of Climate Change Mitigation in Indonesia raises various positive aspects ranging from changes in people's lifestyles and presenting good awareness.